2020
DOI: 10.1101/2020.03.27.012047
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Ultrafast and accurate 16S microbial community analysis using Kraken 2

Abstract: For decades, 16S ribosomal RNA sequencing has been the primary means for identifying the bacterial species present in a sample with unknown composition. One of the most widely-used tools for this purpose today is the QIIME (Quantitative Insights Into Microbial Ecology) package. Recent results have shown that the newest release, QIIME 2, has higher accuracy than QIIME, MAPseq, and mothur when classifying bacterial genera from simulated human gut, ocean, and soil metagenomes, although QIIME 2 also proved to be t… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…In order to compare changes in the abundance of opportunistic pathogens at the species level after surgery across cohorts, 16S rRNA gene datasets were taxonomically classified using the Kraken2 pipeline in addition to the metagenomic datasets. Recent work by Lu et al 45 showed that classification of 16S rRNA gene microbial communities using Kraken2 is fast and accurate.…”
Section: Comparative Integrated Analysis Across Multiple Datasetsmentioning
confidence: 99%
“…In order to compare changes in the abundance of opportunistic pathogens at the species level after surgery across cohorts, 16S rRNA gene datasets were taxonomically classified using the Kraken2 pipeline in addition to the metagenomic datasets. Recent work by Lu et al 45 showed that classification of 16S rRNA gene microbial communities using Kraken2 is fast and accurate.…”
Section: Comparative Integrated Analysis Across Multiple Datasetsmentioning
confidence: 99%
“…Yet another group of tools directly classifies sequencing reads into taxonomic bins without OTU/ASV generation. These tools are typically used for shotgun metagenomics but sometimes also for amplicon analysis, e.g., MEGAN (Mitra et al, 2011), Kraken2 (Lu and Salzberg, 2020) or Centrifuge (Cuscó et al, 2018;Khachatryan et al, 2020). Recovering representative sequences such as OTUs or ASVs allows for further analysis like constructing phylogenetic trees or performing targeted analyses, such as searching for the same sequence or related sequences in other data sets, that is not possible when using direct read classification.…”
Section: Introductionmentioning
confidence: 99%
“…In order to compare changes in the abundance of opportunistic pathogens at the species level after surgery across cohorts, 16S rRNA gene datasets were taxonomically classified using the Kraken2 pipeline in addition to the metagenomic datasets. Recent work by Lu et al 2020 [28] showed that classification of 16S rRNA gene microbial communities using Kraken2 is fast and accurate.…”
Section: Methodsmentioning
confidence: 99%